The dilemmas of relevance: exploring the role of Natural resources and Energy Consumption in managing climate crisis in Africa - Olatunji Abdul Shobande; Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
The study examines the role of natural resources and energy consumption in managing the climate crisis in Africa, using annual series data from the World Bank from 1980 to 2019. The empirical strategy is based on the second-generation panel techniques that account for cross-sectional dependency in the series. Specifically, the empirical evidence is based on the Westerlund (2017) panel cointegration test, panel augmented mean group, common correlated effects mean group and the vector autoregressive-vector error correction approach. Evidence from the panel analysis confirmed the existence of Carbon Kuznets Curve (CKC) U-shaped nexus in Africa, but the country-level results are mixed. Furthermore, results using the vector autoregressive-vector correction model indicate possible convergence among the variables across the African countries. Natural resource unidirectionally Granger-causes carbon emissions. We suggest the consideration of environmental factors in the utilisation of natural resources. Similarly, energy efficiency is crucial to decouple carbon from energy usage. The study complements the extant literature by assessing the role of natural resources and energy consumption in managing climate crisis in Africa.
Keywords: 330; Carbon Kuznets Curve; carbon emission; Natural resource; climate crisis; energy consumption; Africa